The determinant of foreign direct investment in ASEAN : a semi-gravity approach. - Ismail, Normaz Wana (Springer, 2009)

(untitled)
This study used a semi gravity model to identify the determinants of FDI in ASEAN countries. The results revealed that besides the market size for host and source country, other criteria such as the shorter the distance, common in language and border, the extended market relative to distance also attracts more foreign investors. Other macroeconomic factors such as lower inflation rate, the slightly higher in exchange rate and good management of the government budget are among the key factors that attract more FDI. In addition to economic factors, social factors such as good telecommunication and infrastructure and non-economic factors such transparency and trade policy also encourage more investors to the ASEAN.